Pony feeding management: the role of morphology and hay feeding methods on intake rate, ingestive behaviors and mouth shaping - Bordin, Clara; Raspa, Federica; Greppi, Martina; Harris, Patricia; Ellis, Andrea Dorothea; Roggero, Angela; Palestrini, Claudia; Cavallini, Damiano; Bergero, Domenico; Valle, Emanuela (Frontiers in Veterinary Science, 2024)
In the last decade, haynets and slow feeders have been promoted as sustainable tools to improve the feeding management of horses and reduce forage waste, but little is known about their effects on ponies. Therefore, the aim of this study was to analyze the effects of different hay feeding methods on the ingestive behaviors, intake rate and mouth shaping of ponies belonging to two breed types, which are characterized by different head morphologies. Shetland type (SH, n = 5) and Welsh/Cob type (WC, n = 4) ponies were fed hay using four feeding methods: on the ground (G), a fully filled haynet (HF), a partially filled haynet (HL), and a slow-feeder hay box (HB). Head morphology was measured for each pony. Video recordings were then made to apply geometric morphometrics and to perform behavioral analysis. The intake rate was measured for each pony and each feeding method. Data obtained with geometric morphometrics were analyzed using principal component analysis (PCA) and canonical variate analysis (CVA). Behavioral data and intake rate measurements were analyzed using a mixed model, a post-hoc Tukey’s test, a Pearson’s correlation test, and a stepwise regression model. The geometric morphometrics results demonstrated that feeding method influenced mouth shaping (36% for G, 78% for HB, 77% for HF, 83% for HL, considering the total variance of shape) and affected the intake rate. Differences in mouth shaping and ingestive behaviors in SH and WC ponies also confirmed the role of morphology in feeding management. The HL proved to be the most effective tool to increase feeding consumption time when needed (5 h/kg for SH ponies and 3 h/kg for WC ponies, considering the intake time), although the HB may be the optimal choice to reduce the intake rate while maintaining a more natural posture. Future studies are suggested to fully understand how body size and morphology influence feeding in equine species.